Depressive symptoms in Parkinson's disease are related to reduced [123I]FP-CIT binding in the caudate nucleus. Issue 2 (29th June 2013) - Vriend, Chris; Raijmakers, Pieter; Veltman, Dick J; van Dijk, Karin D; van der Werf, Ysbrand D; Foncke, Elisabeth M J; Smit, Jan H; Berendse, Henk W; van den Heuvel, Odile A
Abstract : Background: Depression is a common neuropsychiatric symptom in Parkinson's disease (PD). In previous research, PD-related depression was associated with striatal dopaminergic deficits, presumably due to degeneration of brainstem dopaminergic projections. Segregated areas of the striatum are crucially involved in various parallelly arranged cortical-striatal-thalamocortical circuits and serve functions in, among others, motor control or emotion. This suggests regional specificity of dopaminergic deficits in the striatum in motor and depressive symptoms in PD. Methods: In this cross-sectional retrospective study, we correlated severity scores of depressive and motor symptoms in 100 non-demented PD patients (median Hoehn & Yahr stage: 2) with dopamine loss in specific regions of the striatum as measured by [ 123 I]FP-CIT SPECT tracer binding to the dopamine transporter (DaT). Results: Depressive symptoms were related to lower DaT binding in the right caudate nucleus, while motor symptoms were associated with decreased DaT binding in the right putamen. This double dissociation was most pronounced in early-stage PD patients. Conclusions: These results suggest that depressive symptoms in PD are associated with dopamine loss in the caudate nucleus, possibly related to degeneration of dopaminergic projections from the ventral tegmental area, while motor symptoms are associated with low dopamine signalling to the putamen and loss of nigrostriatal projections. This is consistent with the neuroanatomy of partially segregated cortical-striatal-thalamocortical circuits and supports the role of dysfunctional associative and motivational circuits in PD-related depression.